Strategi Penyebaran Informasi Publik Melalui Video Digital: Proses Penyuntingan dan Standar Konten di Dinas Komunikasi dan Informatika Pemerintah Provinsi Sumatera Barat - Raihana Salsabillah; Marlini Marlini; Rini Asmara (Program Studi Ilmu Perpustakaan dan Informasi Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2025)
Introduction. The dissemination of public information through digital video at the Office of Communication, Informatics, and Statistics (Diskominfotik) of West Sumatra Province focuses on the editing process and the content standards applied. This study is important because digital video has become a primary medium for government communication in delivering information to the public in a fast, accurate, and transparent manner in the digital era. Data Collection Methods. This study employed a descriptive qualitative approach, with data collected through in-depth interviews with three informants who were directly involved in the video content production process. Data Analysis. Data were analyzed through stages of observation, interviews, data reduction, and conclusion drawing to obtain a comprehensive understanding of the workflow of the video editing process. Results and Discussion. The findings indicate that the video editing process at Diskominfotik is conducted based on Standard Operating Procedures (SOPs) that refer to public information disclosure regulations and government communication ethics. The editing stages include footage selection, message structuring, voice-over recording, subtitle insertion, and multi-level review by relevant officials as a form of information gatekeeping. Technical obstacles such as audio quality issues, field conditions, and visual synchronization problems are addressed through editing techniques and content adjustments. Conclusion. The video production strategy implemented by Diskominfotik is effective in enhancing the accuracy, accessibility, and effectiveness of public information dissemination. Future studies are recommended to examine audience perceptions of government video content.